Towards Low-Latency Byzantine Agreement Protocols Using RDMA - Schwarz-Rüsch, Signe; Messadi, Ines; Kapitza, Rüdiger (Proceedings - 48th Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops, DSN-W 2018, 2018)
Byzantine fault tolerance (BFT) protocols can mitigate attacks and errors and are increasingly investigated as consensus protocols in blockchains. However, they are traditionally considered costly in terms of message complexity and latency due to the required multiple rounds of message exchanges. With the availability of Remote Direct Memory Access (RDMA) in data centers, message exchange latency can be reduced compared to TCP, as RDMA enables kernel bypassing and thereby avoids intermediate data copying. Retaining the performance benefits for RDMA during its integration, however, is non-trivial and error-prone. While the use of RDMA has previously been explored for key/value stores, databases and distributed file systems, agreement protocols especially for BFT have so far been neglected. We investigate the usage of RDMA in the Reptor BFT protocol for low-latency agreement and show first steps towards an RDMA-enabled consensus protocol. For this, we present Rubin, a framework offering similar functionality to the Java NIO selector, which can handle multiple network connections efficiently with a single thread and is employed in several BFT protocol implementations such as BFT-SMaRt and UpRight.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Blockchain Consensus; Byzantine Fault Tolerance; Remote Direct Memory Access